Attitude and Awareness of Dentists Towards Resin-Bonded Bridges in Benghazi, Libya - Alsaeidi, Maryam; Ghadi Albarghathi; Hajer Ghaleiw; Rubyan Fituri (AlQalam Journal of Medical and Applied Sciences, 2025)
Resin-bonded bridges offer a simple and conservative approach to tooth replacement. However, the use of this treatment option has been limited in terms of practicality and effectiveness. Therefore, this study aimed to evaluate the attitude and awareness of dentists towards resin-bonded bridges (RBBs) in Benghazi. An online survey was conducted with 200 dentists registered with the Libyan Dental Syndicate. A structured questionnaire, adapted from previous studies, was distributed through Google Forms to gather data on demographics, professional qualifications, attitudes, and awareness of resin-bonded bridges. The data were analyzed using SPSS version 25.0. Out of 300 distributed questionnaires, 200 dentists responded, giving a response rate of 67%. A majority, 83.8% of specialists and 88.1% of general dental practitioners, used RBBs in <10% of their prosthodontics cases. A total of 94.9% of SPs and 67.3% of GPs considered RBBs as a provisional restoration. Additionally, the participants, 98% of SPs and 83.2% of GPs regarded debonding as the biggest disadvantage of RBBs. Focused educational programs and hands-on training in resin-bonded bridges are needed to bridge the gap between theoretical knowledge and clinical application of RBBs. These efforts will empower GPs and SPs in Benghazi, leading to better patient outcomes and expanding restorative treatment options.